The Panic Buying Behavior of Consumers During the COVID-19 Pandemic: Examining the Influences of Uncertainty, Perceptions of Severity, Perceptions of Scarcity, and Anxiety - Nor Asiah Omar; Mohd Helmi Ali; Syed Shah Alam; Muhamad Azrin Nazri (Elsevier, 2024)
Indexed by WOS/SCOPUS/ERA